2013
DOI: 10.1016/j.envint.2012.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of fluorotelomer compound to perfluorocarboxylates in humans

Abstract: Levels of perfluorocarboxylates (PFCAs) in biological compartments have been known for some time but their transport routes and distribution patterns are not properly elucidated. The opinions diverge whether the exposure of the general population occurs indirect through precursors or direct via PFCAs. Previous results showed that ski wax technicians are exposed to levels up to 92 000 ng/m(3) of 8:2 fluorotelomer alcohol (FTOH) via air and have elevated blood levels of PFCAs. Blood samples were collected in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(89 citation statements)
references
References 41 publications
4
85
0
Order By: Relevance
“…Intensive research has been conducted to study their sources, fate, transport, and distribution in environmental media, human exposure, and ways to reduce the health risks. Fluorotelomer alcohols (FTOHs) are major precursors of PFCAs and other related compounds because FTOHs can ultimately degrade to form PFCAs through atmospheric oxidation Young and Mabury, 2010) and biodegradation (Nilsson et al, 2013;Butt et al, 2014). In addition, 1H,1H,2H,2H-perfluoro-1-octanol (6:2 FTOH) and 1H,1H,2H,2H-perfluoro-1-decanol (8:2 FTOH) have also been found to be estrogenic (Maras et al, 2006;Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Intensive research has been conducted to study their sources, fate, transport, and distribution in environmental media, human exposure, and ways to reduce the health risks. Fluorotelomer alcohols (FTOHs) are major precursors of PFCAs and other related compounds because FTOHs can ultimately degrade to form PFCAs through atmospheric oxidation Young and Mabury, 2010) and biodegradation (Nilsson et al, 2013;Butt et al, 2014). In addition, 1H,1H,2H,2H-perfluoro-1-octanol (6:2 FTOH) and 1H,1H,2H,2H-perfluoro-1-decanol (8:2 FTOH) have also been found to be estrogenic (Maras et al, 2006;Liu et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Other transient metabolites (a-OH 5:3 acid, 5:2 Uacid, and 5:2 Uacid) were only detected sporadically among the different experimental systems at low levels (<0.15 mol% together). 5:3 acid was also detected in serum samples of ski-wax workers exposed to 6:2 FTOH via inhalation (Nilsson et al, 2013).…”
Section: Observed Metabolites From Rat Microsomal Biotransformationmentioning
confidence: 86%
“…[F(CF 2 ) 7 CH 2 CH 2 COOH], and to a less extent PFNA (perfluorononanoic acid) (Martin et al, 2005;Fasano et al, 2006;Nabb et al, 2007;Nilsson et al, 2013). Historically, 5000-6000 t per year equivalent of perfluoroalkyl iodide was manufactured globally between 2000 and 2002 (Prevedouros et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Much attention has been paid to the metabolism of FTOHs in different biological systems. 4,5,19 However, limited information is available on the metabolic pathways in plants. In this study, phase I and phase II metabolism of 8:2 FTOH in soybean were revealed.…”
Section: Concentrations Of 8:2 Ftoh and Its Degradation Products In Smentioning
confidence: 99%
“…In the homologous series of FTOHs, 8:2 FTOH has historically been produced in the largest volume. Degradation of 8:2 FTOH by oxidation in the atmosphere, 9,10 photolysis in aqueous environments, 11 aerobic and anaerobic microbial biodegradation in terrestrial environments, 12−14 and in vivo and in vitro metabolism in animals 15−18 and in humans 19,20 has been reported. The 8:2 FTOH degradation in different matrixes shares some common steps, proceeding via saturated and unsaturated fluorotelomer carboxylic acid intermediates, which are finally oxidized to PFCAs as the terminal products.…”
Section: ■ Introductionmentioning
confidence: 99%